Effect of Kankrej Cow Urine Distillate and Panchgavya Supplementation on Growth Performance, Carcass Characteristics and Blood Biochemical Profile of Broiler Chickens - Patel, H. V.; Patil, S. S.; Pawar, M. M.; Ankuya, K. J.; Parmar, R. S.; Modi, C. P.; Ashwar, B. K. (International Journal of Bio-resource and Stress Management, 2024)
A study was conducted during the month of December, 2023 and January, 2024 to evaluate the effect of cow urine distillate and Panchgavya supplementation on growth performance, nutrient digestibility, carcass characteristics and blood biochemical parameters of broiler chickens. A total of 200 day-old broiler chicks were uniformly distributed into four treatment groups with 50 birds per treatment for a period of 42 days. The dietary treatments were T1: Basal diet, T2: Basal diet+1 ml cow urine distillate (CUD) in drinking water bird-1 day-1, T3: Basal diet+1 ml Panchgavya in drinking water bird-1 day-1 and T4: Basal diet+50 mg of Commercial feed grade antibiotic (Tylosin phosphate) kg-1 of feed. Results revealed that the mean final body weight and body weight gain in broiler chickens were not influenced by the inclusion of CUD and Panchgavya. There was no effect on feed intake, nutrient digestibility, carcass characteristics and blood biochemical parameters due to CUD and Panchgavya supplementation in broiler chickens. The feed conversion ratio was better in Panchgavya and feed antibiotic groups than the control group. The serum cholesterol level was significantly (p<0.05) reduced in Panchgavya and feed antibiotic groups followed by CUD group than the control. It may be concluded that supplementation cow urine distillate and Panchgavya in broiler chickens did not influence growth performance, feed intake, nutrient digestibility, carcass characteristics and blood biochemical parameters. Panchgavya and feed antibiotic supplementation improved feed conversion ratio and reduced serum cholesterol level in broiler chickens.